A study of effect of tarsal tunnel decompression on sensory improvement in diabetic foot: a prospective randomized control trial - S., Lakshmanan; M. S., Viswanathan; Anbazhagan, R. (International Surgery Journal, 2018)
Background: In India approximately, 45000 legs are amputated every year and almost 75% of these amputations are carried out in neuropathic feet which are potentially preventable. Diabetic peripheral nerves are at risk of entrapment neuropathies focally, where these nerves are contained in a closed space. The aim of the study was to find out the effect of decompression of compressed posterior tibial nerve and its branches at tarsal tunnel in restoration of sensation in diabetic foot. Methods: A total of 70 diabetic patients with ulcer foot in one limb (test limb) and with no ulcer on the other limb (control limb) were selected for study. The test limb was subjected to tarsal tunnel release. Sensory recovery was evaluated in the ulcer limb and compared with normal limb in same patient and results were evaluated statistically for significance. Results: Present study shows that following tarsal tunnel decompression surgery on test limb, 65 patients (93%) had sensory gain and 5 patients (7%) had documented no sensory gain on test limb, with statistical significance. After de-compressive surgery on the test limb, 69 patients (98.6%) were documented to have resolving of Tinel sign in the test limb with sensory improvement, suggesting adequate decompression and 1 patient (1.4%) was documented to have persistent Tinel sign suggesting possibility of inadequate decompression with no recovery of sensation, with statistical significance. Conclusions: Present study reveals that decompression of tarsal tunnel in diabetic ulcer foot patients leads to definite improvement in sensation of foot which will prevent further ulcer formation and resultant complications ending in amputations.